ʿAttīḏ-Compounds in Middle Aramaic: Discursive Functions and Tense-Aspect-Modal Characteristics. (24th August 2022) - Tsolin, Dmytro
Abstract: Despite the frequent use of ʿattīḏ -compounds in Middle Aramaic, 1 their syntactic and discourse functions as well as the tense-aspect-modal (TAM) characteristics are represented in modern works on Aramaic grammar in a rather fragmentary fashion. On the whole, ʿattīḏ -compounds are considered as competing with yiqṭul -imperfect periphrastic verbal forms that function predominantly in prophetic discourse with the meaning of distant future. However, the range of the discourse functions of ʿattīḏ -compounds goes beyond the scope of prophecy and their TAM-characteristics need to be reconsidered. In this article, compounds with an ʿattīḏ -auxiliary are viewed as possessing the modal meaning of intention originally, and it is this distinctive seme that determines other specificities of their functions. This paper presents the results of cross-dialectical analysis of ʿattīḏ- compounds in Jewish Aramaic dialects, Samaritan Aramaic, Classical Syriac and Christian Palestinian Aramaic, and includes biblical texts translated from Hebrew as well as the original writings in these Middle Aramaic languages.